(untitled) (REMUNOM, 2025)
This study analyzes the quality of public spending in Brazil over the past ten years (2014–2024) through a narrative literature review, identifying challenges, advances, and future perspectives in the efficient allocation and management of public resources. The findings highlight that education is the predominant focus in studies on public spending, reflecting its strategic importance for socioeconomic development. However, inefficiencies persist, such as unequal resource allocation, weak planning, and administrative obstacles, including the cancellation of expenditures and concentration of fiscal execution at the end of budget cycles. These issues contribute to regional disparities and hinder the achievement of desired results, particularly in improving public services. Although investments in education have increased, studies reveal that financial efforts alone do not ensure efficiency or quality outcomes. The analysis emphasizes the need for enhanced governance, transparency, and accountability to optimize resource allocation and meet societal demands. Strengthening monitoring and evaluation mechanisms, alongside evidence-based policies, is essential for improving the efficiency and effectiveness of public spending. This study concludes that addressing structural challenges is crucial to promoting equitable development, reducing inequalities, and ensuring that public spending effectively contributes to the population’s well-being and Brazil’s sustainable growth.